Analysis of the marginal abatement cost curve for ammonia emissions: addressing farm system heterogeneity - O.R. Ogunpaimo; C. Buckley; S. Hynes; S. O’Neill (Irish Journal of Agricultural and Food Research)
Agriculture is responsible for 99.4% of ammonia (NH3) emissions in the Republic of Ireland and the country has failed to comply with limits set down by the European Union National Emissions Ceiling Directive (NECD) for 9 of the last 11 reporting years. Hence, there exists an urgent need to reduce NH3 emissions to control air pollution and moderate other related environmental and health hazards. This study carries out farm-level marginal abatement cost curve analysis across different farm typologies in the Republic of Ireland. The study also addresses the interactions amongst the considered abatement options and explores the presence of farm system heterogeneity. This allows an assessment as to whether it is sub-optimal to adopt a mitigation measure across different farm systems. Findings indicate that the measures examined in this study are effective in abating NH3 emissions at varying levels across the different farm typologies. Ammonia mitigation measures such as liming, switching to protected urea and a crude protein reduction in livestock diets were primarily cost-saving while the increased clover measure moved between cost-saving and cost-positive depending on the farm system type. The presence of heterogeneity across the farm typologies was generally supported in this study, highlighting that optimal policy design should be tailored to reflect farms’ characteristics. Furthermore, a lower abatement potential was reported for the combined implementation of selected mitigation measures compared to the sum of individual measures due to interaction effects.